Training on Making Fermented Rice Straw for Animal Feed in Nepo Village, Wonomulyo District, Polewali Mandar Regency - Susanti S, Irma; Khatifah, Khatifah; Nuraliah, Siti; Suhartina, Suhartina; M. Masdi, M. Masdi; A. Sabambang, A. Sabambang; M. Mustari, M. Mustari; Indrawan, Indrawan; F. Najah, F. Najah (Asian Journal of Community Services, 2023)
Training on making fermented rice straw for animal feed in Desa Nepo Kecamatan Wonomulyo Kabupaten Polewali Mandar aims to provide understanding to the community about making fermented rice straw for animal feed. The methods used include providing education regarding fermentation technology for rice straw waste, then discussions with participants regarding the problem that occur and obstacles in handling agricultural waste, and finally direct training in making fermented rice straw. The result of this community service activity is that participants know how to make fermented rice straw for animal feed. The conclusion of the community service activities in Desa Nepo is that the participants were able to learn about fermentation technology that can be used to process rice straw waste into highly nutritious animal feed.